Three seconds [compact disc, unabridged] - Roslund, Anders, 1961- (Brilliance Audio, 2010)
Piet Hoffman is the Swedish police's most valuable secret operative. His cover is that of a lieutenant inside the ruthless Polish mafia trying to take over amphetamine distribution within Sweden's prison system. When a botched drug deal involving Hoffman results in the cold-blooded killing of a police informant, the investigation, assigned to the brilliant but haunted Detective Inspector Ewert Grens, leads to a string of unsolved cases in which key information has been withheld.